Start-up team’s collective cognitive schemas in nascent markets - Purosto, Joanna (My University, 2023)
In their early stages, start-ups often modify their business model to innovate and align their scarce internal resources to the evolving market needs. In essence, a business model is a cognitive schema that is shared across the start-up team members. It is this collective understanding of the business model that determines the start-up’s success. However, there is a lack of studies investigating how a mutually recognized business model takes shape through a learning process in nascent markets when there is just a vague idea of an arising market need. To fill the research gap, this study draws on a qualitative multiple-case study based on interviews with three start-up key decision-makers from two start-ups. Data collection combined narrative, visual, and interview methods. In the first phase of the interview, interviewees described their company story from inception to this date. Only a little guidance was given for the first phase to not steer the founding story, but to give more room for surprising findings. In addition to describing the story, Company A’s interviewees complemented their story by drawing a visual timeline on a whiteboard. The second interview phase was conducted as a semi-structured interview with pre-defined main questions and spontaneous follow-up questions. The empirical research supports the existing literature to a large extent and provides further findings on forming a collective cognitive schema in nascent markets. The study's findings align with the current research in that start-up teams learn about nascent markets like pre-schoolers. The theoretical framework of Parallel Play explains that start-ups, like pre-schoolers, learn about the new world by playing next to each other, engaging in hands-on experimenting, and pausing before elaborating on a certain activity system. Further, the 4I organizational learning framework offers depth for organizational-level learning in business model design. It explains how case companies transform learnings from individual intuiting by first interpreting them with the team and then integrating the learning as part of their operations. In addition to aligning with the current literature, results showed that perception is required to introduce individual’s insights on an organizational level to shape a business model. According to the empirical findings, a business model seems to be a collective cognitive schema organized into categories. This research explores the Piagetian stage theory to conceptualize how collective cognitive schemas take shape. The Piagetian stage theory is generally applied in child development, and it describes that 2- to 7-year-old children organize their understanding through categorization; they learn to sort and group objects and experiences based on shared characteristics. Start-ups, like pre-schoolers, need to learn to categorize new information when facing new situations in nascent markets, such as composing their business model. Overall, this research contributes to the current literature by offering a deeper understanding of the business model design in nascent markets and explains how collective cognitive schemas take shape in the new venture learning process.
Keywords: start-up, nascent market, business model